SELECTION VALUE OF CORN VARIETY DIVERSITY OF USTYMIVKA EXPERIMENTAL PLANT GROWING STATION COLLECTION - Kharchenko, Yu. V.; Kharchenko, L. Ya.; Kutsenko, O. M.; Liashenko, V. V. (Scientific Progress & Innovations, 2020)
The expediency of creating self-pollinated lines of a new generation is presented in the article. To achieve this aim it is necessary to ensure the selection requirements in the initial material having broad ge- netic basis and high adaptability. New lines can be obtained from the best local and selection varieties, pop- ulations, early-ripening and mid-early hybrids of the world and Ukrainian selection, synthetic populations, and also late-ripening varieties and races from southern countries. Field experiments were conducted at Ustymivka experimental plant growing station in 5-field crop rotation in 2014–2019. 300 local corn selec- tion varieties and populations of various ecological and geographical origins from 16 countries of the world served the material for studies. The experiments were conducted under the following conditions: the back- ground – black fallow land; cultivation technology included timely performing the complex of agro-technical measures of soil tillage and handling plants, typical for the Left-Bank Forest-Steppe zone of Ukraine; sowing was conducted at the end of April or beginning of May in double blocks; the plot area was 4.9 m2; the fol- lowing standards were used: Kharkivskyi 193 MB, Kharkivskyi 295 MB, and Kharkivskyi 313 MB hybrids. The applied study methods enabled to differentiate the collection samples and single out the most valuable ones, as sources of economic and selection valuable signs according to different directions of selection using – yield and its components, product quality, resistance to stress climatic factors, etc. As a result of studying the collection of corn genetic resources, the “Catalogue of genetic diversity of corn ancient, local, selection varieties and populations (Zea Mays L.), at Ustymivka experimental plant growing station collection” was created. The collection genetic resources was certified, and work on systematizing and grouping the samples according to their origin, methods of creation, botanical taxonomy, groups of value ( by the classifier) was conducted. Each sample is provided with available standard grain. The majority of seeds were put for long- term storage. Each sample was given the National Catalogue of Ukraine number.